EXTERNAL DEBT SERVICING AND INTEREST RATE IN NIGERIA 2000-2023 (Journal of the Management Sciences, 2025)
This study examines the effect of debt servicing on interest rates in Nigeria from 2000 to 2022. Time series data were obtained from the Central Bank of Nigeria Statistical Bulletin, and the analysis was conducted using the Ordinary Least Squares (OLS) regression technique. The findings reveal that external debt servicing exerts a negative and significant influence on interest rates in Nigeria during the study period. This suggests that rising external debt obligations constrain financial resources and limit the government's borrowing capacity. The study concludes that the persistent burden of external debt servicing may hinder economic stability and fiscal flexibility. It therefore recommends that the government enhance domestic revenue generation through improved tax administration and an expanded tax base to reduce dependence on external borrowing. Additionally, debt financing should be strategically directed toward promoting economic diversification beyond the oil sector to mitigate vulnerability to external debt pressures.
Keywords: External debt; Debt servicing; Interest rate; Nigeria